Modus Of Operandi and Sanctions For Criminal Actions In The Health Field (Study Decision Number 90/Pid.Sus/2023/Pn Mks) - Th. Timbonga, Yotham (UNES Law Review, 2023)
The aim of this research is to determine the modus operandi of criminal acts in the health sector (study of decision Number 90/Pid.Sus/2023/PN Mks) and the judge's legal considerations in handing down decision Number 90/Pid.Sus/2023/PN Mks. This research was conducted using a type of normative legal research with the approach method in this research being the statutory regulation approach. The conclusions of this research are: 1) The modus operandi carried out by the defendant who was a distributor of pharmaceutical preparations without a distribution permit in Decision Number 90/Pid.Sus/2023/PN Mks was by buying the drug from his friend secretly or secretly, then hiding it. the medicines are taken to their home first and the aim is to distribute them to consumers and make a profit from selling pharmaceutical preparations without a distribution permit. 2) The judge's consideration in imposing a criminal sentence on the perpetrator in Decision Number 90/Pid.Sus/2023/PN Mks is based on both juridical and non-juridical considerations. The judge's imposition of sanctions is based more on the facts of the trial and valid evidence and takes into account demands of the Public Prosecutor. The sentence imposed in the form of imprisonment for 1 (one) year and 10 (ten) months on the defendant is sufficient to have a deterrent effect on the perpetrator so that he does not repeat his actions again.